The Strategy for Attracting and Engaging Talent to Increase the Competitiveness of the Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): What should the strategy for attracting and engaging talent be in order to increase competitiveness?Objective: The aim of this research is to explore effective strategies for attracting and engaging talent that enable organizations to remain competitive in the market. The main goal of this seminar paper is to identify and analyze strategies that help organizations in acquiring and integrating high-quality talent.Method: We used a qualitative research method based on the systematic study of existing literature, professional works, and articles. Based on this, we will provide opinions and suggestions for possible improvements.Results: The foundation of any organization is its people. Organizations that approach recruitment systematically will have more engaged and productive employees with lower turnover rates. According to the EFQM model, employees will be better aligned with the organization's strategic goals, leading to greater efficiency, customer satisfaction, and sustainable business development. In this way, companies will become more attractive employers and secure a competitive advantage in the market.Organization: HR strategies play a key role in achieving competitive advantage. An organization can approach talent management more focused and strategically, which will improve its adaptability, innovation, and long-term success.Society: An effective strategy for attracting and engaging talent not only impacts the organization but also reduces unemployment, enhances employee satisfaction, and fosters innovation.Originality: This research brings practical value to organizations that aim to improve their HR strategy and increase competitiveness.Limitations/further research: We focused on similar studies and references already conducted in this area. Further research in this field is recommended.
Keywords: organization; human resources; attraction; engagement; employees; EFQM model